2009
DOI: 10.1007/s00128-009-9792-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Traffic-Related Pollution in a Province of Central Italy with Transplanted Lichen Pseudovernia furfuracea

Abstract: The ability of transplanted lichen Pseudevernia furfuracea to biomonitor specific airborne pollutants (heavy metals and polycyclic aromatic hydrocarbons—PAHs) was investigated at five stations with different traffic densities in Viterbo, Italy. Exposed lichen showed high levels of all analysed pollutants; greatest values were for Zn (147–252 μg/g dw), Pb (24.9–34.6 μg/g dw), fluoranthene (37–107 ng/g dw), pyrene (23–124 ng/g dw). Comparison between contaminants concentration in lichens before and after exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 15 publications
2
24
1
1
Order By: Relevance
“…It has been reported that the fruticose lichens absorb the low molecular weight POPs better, most likely due to their high surface area to volume ratio, whilst the foliose lichens preferentially absorb the higher molecular weight organic pollutants [34,45,46,47]. Despite these differences, it has been found that similar POP profiles have emerged from studies, where 2-to 4-ringed PAHs are primarily observed in PAH studies with lichens [36,37,38,42,43,44,48,49,50] and the PCDD/F profiles show a tendency towards TeCDD/PeCDD and PeCDF domination [39,41,46,51]. Blasco et al [34] investigated the behavior of different lichen species under the same conditions with regard to their abilities to accumulate PAHs.…”
Section: Biomonitoring Of Organic Air Pollutants Using Lichensmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the fruticose lichens absorb the low molecular weight POPs better, most likely due to their high surface area to volume ratio, whilst the foliose lichens preferentially absorb the higher molecular weight organic pollutants [34,45,46,47]. Despite these differences, it has been found that similar POP profiles have emerged from studies, where 2-to 4-ringed PAHs are primarily observed in PAH studies with lichens [36,37,38,42,43,44,48,49,50] and the PCDD/F profiles show a tendency towards TeCDD/PeCDD and PeCDF domination [39,41,46,51]. Blasco et al [34] investigated the behavior of different lichen species under the same conditions with regard to their abilities to accumulate PAHs.…”
Section: Biomonitoring Of Organic Air Pollutants Using Lichensmentioning
confidence: 99%
“…Whereas Guidotti et al [44,49] used cyclohexane as the solvent for ultrasound assisted extraction, combining only 2 extractions, Domeno et al [50] extracted a 0.2 g lichen sample using portions of 15 mL dichloromethane each in four subsequent extractions. A study in which a novel ultrasonic assisted extraction technique for lichens was developed by Domeno and Blasco [50], found that hexane is the solvent which extracts most PAHs efficiently and the new DSASE technique has been popular in numerous [34,36,37,68] studies since [34,42,68].…”
Section: Pressurized Liquid Extraction (Ple) Has Been Employed By Schmentioning
confidence: 99%
“…Lichens have been well studied as a biomonitoring tool for air pollution [9][10][11][12][13]. The lichens absorb mineral nutrients and trace elements, including metals from dry and wet atmospheric deposition, due to the lack of a protective cuticle and a vascular root system [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have used the technique of lichen transplantation to monitor air pollution, and shortterm transplantations may be an easy and economical method to monitor airborne pollutants (Canas et al, 1997). In Turkey, a large number of pollution-monitoring studies that have used biological and chemical methods have shown the ability of lichens to absorb elements directly from the air and accumulate them in their tissues (Cansaran-Duman et al, 2009, Guidotti et al, 2009Cansaran-Duman, 2011;Aslan et al, 2004Aslan et al, , 2010Aslan et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%